Resin-based hard carbon material, preparation method thereof, negative plate and battery

By mixing graphene/carbon nanotube aerogel with resin, resin-based hard carbon materials with high rate performance and cyclic properties are prepared, which solves the problem of insufficient performance of existing resin-based hard carbon materials in high-power charging and discharge scenarios, and achieves high-performance applications suitable for sodium ion batteries.

CN119822358APending Publication Date: 2025-04-15JIANGSU TIANHE ENERGY STORAGE CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510060405.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-15
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The current resin-based hard carbon materials have insufficient rate performance and cycling performance in high-power charging and discharging scenarios, making it difficult to meet the high-performance needs of sodium ion batteries.

Method used

By mixing graphene/carbon nanotube aerogel with resin, impregnation, heat treatment and pre-carbonization treatment, resin-based hard carbon materials with high rate and cyclic properties were prepared.

Benefits of technology

While ensuring compaction density, the rate performance and circulation performance of hard carbon negative electrode materials are significantly improved, and are suitable for high-performance applications of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005242704100000141
    Figure BDA0005242704100000141
  • Figure BDA0005242704100000151
    Figure BDA0005242704100000151
  • Figure BDA0005242704100000152
    Figure BDA0005242704100000152
Patent Text Reader

Abstract

The invention provides a resin-based hard carbon material and a preparation method thereof, a negative plate and a battery. The method comprises the following steps: mixing graphene / carbon nanotube aerogel with resin, and carrying out impregnation, heat treatment and pre-carbonization to obtain a resin-based hard carbon precursor; and performing crushing and carbonization treatment on the resin-based hard carbon precursor to obtain the resin-based hard carbon material. The resin-based hard carbon material prepared by the method provided by the invention has excellent rate capability and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a resin-based hard carbon material and a preparation method thereof, a negative electrode sheet and a battery. Background Art

[0002] With the penetration of new energy, more and more application scenarios require the use of electrochemical energy storage products. At present, electrochemical energy storage is still mainly based on lithium-ion batteries, but there are problems such as limited lithium resources and uneven distribution. It is necessary to find an electrochemical energy storage product that can complement lithium-ion batteries. Sodium-ion batteries and lithium-ion batteries are both alkali metal ion batteries and have similar working principles. In addition, sodium has the advantages of higher abundance and more uniform distribution, which is more suitable for large-scale applications.

[0003] In sodium-ion batteries, the positive electrode is mainly composed of layered oxides, polyanions and Prussian materials, and the negative electrode is mainly composed of hard carbon, soft carbon and alloy materials. In terms of performance and price, hard carbon negative electrodes are more suitable for sodium-ion batteries. Hard carbon negative electrodes are divided into biomass-based, resin-based, asphalt-based and coal-based. Among them, resin-based hard carbon is the preferred precursor for high-performance hard carbon because of its stable raw material source and adjustable composition. However, the poor rate performance of resin-based hard carbon hinders its application in high-power charging and discharging scenarios, and it is urgent to improve its electronic conductivity and ionic conductivity.

[0004] Patent CN117682503A discloses a high-performance resin-based hard carbon negative electrode material and its preparation method and application. The patent uses pore-making and doping technology to prepare a hard carbon negative electrode material with a particle matrix having a relatively large porous structure. When the resin-based hard carbon negative electrode material is used as a negative electrode for a sodium ion battery, it has a large number of porous structures and a fixed chemical composition, and can improve the diffusion kinetics and storage capacity of sodium ions in the hard carbon in the battery, thereby improving the rate performance and power density of the sodium ion battery. However, pore-making will lead to a decrease in the material density, affecting the compaction density of the material.

[0005] Patent CN117069091A discloses a resin-based hard carbon negative electrode material and its preparation method and application. This patent prepares a hard carbon material by pyrolyzing and pre-carbonizing the resin precursor and carbonizing it. Compared with the hard carbon obtained by using a single phenolic resin, the hard carbon material has a wider interlayer spacing, which is conducive to the embedding and intercalation of sodium ions, ensuring good reversibility, improving the first coulomb efficiency, and improving the rate performance and long-cycle stability; at the same time, heteroatom doping can provide more active sites, which is beneficial to improving the sodium storage performance of the hard carbon material and ensuring the improvement of capacity. However, the method of increasing the interlayer spacing has little effect on the improvement of the rate performance. Summary of the invention

[0006] In order to overcome the technical problems in the prior art that increasing the interlayer spacing has little effect on the rate performance, the present invention provides a resin-based hard carbon material and a preparation method thereof, a negative electrode sheet thereof and a battery. The present invention prepares a hard carbon negative electrode material by mixing graphene / carbon nanotube aerogel and resin, thereby improving the rate performance and cycle performance of the hard carbon negative electrode material while ensuring the compaction density.

[0007] Specifically, the first aspect of the present invention provides a method for preparing a resin-based hard carbon material, which comprises the following steps:

[0008] S1, mixing graphene / carbon nanotube aerogel and resin, impregnating, heat treating and pre-carbonizing to obtain a resin-based hard carbon precursor;

[0009] S2. Crushing and carbonizing the resin-based hard carbon precursor to obtain the resin-based hard carbon material.

[0010] In one or more embodiments, the graphene / carbon nanotube aerogel is obtained by freeze-drying and reducing the oxidized graphene / carbon nanotube hydrogel to obtain the graphene / carbon nanotube aerogel.

[0011] In one or more embodiments, the graphene / carbon nanotube hydrogel is obtained by hydrothermally treating an aqueous solution containing graphene oxide, hollow carbon nanotubes and ethylenediamine to obtain the graphene oxide / carbon nanotube hydrogel.

[0012] In one or more embodiments, ethylenediamine is added to a mixed aqueous solution containing graphene oxide and hollow carbon nanotubes to form an aqueous solution containing graphene oxide, hollow carbon nanotubes and ethylenediamine; wherein the mass concentration of graphene oxide in the mixed aqueous solution containing graphene oxide and hollow carbon nanotubes is 1 mg / ml to 8 mg / ml.

[0013] In one or more embodiments, the mass ratio of graphene oxide to hollow carbon nanotubes is (5-20):1.

[0014] In one or more embodiments, the mass of the added graphene oxide is 0.03 g to 0.3 g relative to 1 mL of ethylenediamine.

[0015] In one or more embodiments, the temperature of the hydrothermal treatment is 80-180°C.

[0016] In one or more embodiments, the hydrothermal treatment time is 4-12 hours.

[0017] In one or more embodiments, the freeze drying temperature is -50°C to -60°C.

[0018] In one or more embodiments, the reduction treatment is performed by heating.

[0019] In one or more embodiments, in step S1, the resin is selected from one or more of epoxy resin, phenolic resin, acrylic resin, polyurethane resin, polyester resin, alkyd resin, natural resin, UV resin, silicone resin, polyketone resin, aldehyde-ketone resin, amino resin and fluorocarbon resin.

[0020] In one or more embodiments, in step S1, the impregnation is performed by positive pressure impregnation.

[0021] In one or more embodiments, the positive pressure impregnation pressure is 0.7 MPa to 1.2 MPa, and the impregnation time is 1 to 6 hours.

[0022] In one or more embodiments, in step S1, the temperature of the heat treatment is 90-200°C; and the treatment time of the heat treatment is 0.5-6h.

[0023] In one or more embodiments, in step S1, the pre-carbonization heating temperature is 300-600°C; and the pre-carbonization time is 2-6h.

[0024] In one or more embodiments, in step S2, the Dv50 of the crushed resin-based hard carbon precursor is 3-8 μm.

[0025] In one or more embodiments, in step S2, the heating temperature of the carbonization treatment is 900-1500°C; and the time of the carbonization treatment is 2-6 hours.

[0026] A second aspect of the present invention provides a method for preparing a resin-based hard carbon material, which comprises the following steps:

[0027] (1) mixing graphene oxide and hollow carbon nanotubes in a mass ratio of (5 to 20):1 in water to form a uniformly dispersed aqueous solution of graphene oxide and hollow carbon nanotubes, wherein the mass concentration of graphene oxide in the aqueous solution is 1 mg / ml to 8 mg / ml; adding ethylenediamine solution to the aqueous solution to obtain an aqueous solution of graphene oxide, hollow carbon nanotubes and ethylenediamine; wherein the mass of the added graphene oxide is 0.03 g to 0.3 g relative to 1 mL of ethylenediamine;

[0028] (2) adding the graphene oxide, hollow carbon nanotubes and an aqueous solution of ethylenediamine obtained in step (1) at 100 to 140° C. for 4 to 8 hours to obtain a graphene oxide / carbon nanotube hydrogel;

[0029] (3) freeze-drying the graphene oxide / carbon nanotube hydrogel obtained in step (2) at -50°C to -60°C for 45-52h, and then heating at a power of 500-900W for 10-60s for reduction treatment to obtain a graphene / carbon nanotube aerogel;

[0030] (4) mixing the graphene / carbon nanotube aerogel obtained in step (3) with epoxy resin, impregnating the resulting mixture at a pressure of 0.7 MPa to 1.2 MPa for 2 to 4 h, and then treating at 130 to 180° C. for 0.5 to 3 h to obtain a solidified material, crushing the material to a particle size of less than 1 mm, heating to 300 to 500° C., and pre-carbonizing for 2 to 4 h to obtain a resin-based hard carbon precursor;

[0031] (5) The resin-based hard carbon precursor is crushed to a Dv50 of 3-8 μm, and then carbonized at 1000-1500° C. to obtain the resin-based hard carbon material.

[0032] The third aspect of the present invention provides a resin-based hard carbon material prepared by the method described in any embodiment of the present invention.

[0033] A fourth aspect of the present invention provides a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active material layer, a conductive agent and a binder, wherein the negative electrode active material layer comprises the resin-based hard carbon material as described in any embodiment of the present invention.

[0034] In one or more embodiments, the surface density of the negative electrode active material layer is 2-10 mg / cm 2 , compacted density is 0.8-1.1g / cm 3 .

[0035] A fifth aspect of the present invention provides an alkali metal ion battery, which includes a negative electrode sheet as described in any embodiment of the present invention.

[0036] In one or more embodiments, the alkali metal ion battery is a sodium ion secondary battery.

[0037] The sixth aspect of the present invention provides the use of the resin hard carbon negative electrode material as described in any embodiment of the present invention in improving the rate and cycle performance of a battery.

[0038] A seventh aspect of the present invention provides the use of the resin hard carbon negative electrode material as described in any embodiment of the present invention in the preparation of a sodium ion battery or a lithium ion battery. DETAILED DESCRIPTION

[0039] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in this article. Unless otherwise specified, all technical and scientific terms used in this article are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definitions in this article shall prevail.

[0040] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0041] Herein, “comprising”, “including”, “containing” and similar terms encompass the meanings of “consisting essentially of” and “consisting of”. For example, when “A comprises B and C” is disclosed herein, “A consists essentially of B and C” and “A consists of B and C” should be deemed to be disclosed herein.

[0042] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for brevity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0043] In this document, unless otherwise specified, percentage refers to mass percentage and ratio refers to mass ratio.

[0044] Herein, when describing embodiments or examples, it should be understood that they are not used to limit the present invention to these embodiments or examples. On the contrary, all substitutes, improvements and equivalents of the methods and materials described in the present invention can be included in the scope limited by the claims.

[0045] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0046] In some embodiments, the present invention provides a method for preparing a resin-based hard carbon material, comprising the following steps:

[0047] (1) providing an aqueous solution of graphene oxide, hollow carbon nanotubes and ethylenediamine;

[0048] (2) subjecting the aqueous solution of the graphene oxide, hollow carbon nanotubes and ethylenediamine to hydrothermal treatment to obtain a graphene oxide / carbon nanotube hydrogel;

[0049] (3) freeze-drying and reducing the graphene oxide / carbon nanotube hydrogel to obtain a graphene / carbon nanotube aerogel;

[0050] (4) mixing the graphene / carbon nanotube aerogel and a resin, and then performing impregnation, heat treatment and pre-carbonization treatment to obtain a resin-based hard carbon precursor;

[0051] (5) The resin-based hard carbon precursor is crushed and carbonized to obtain the resin-based hard carbon material.

[0052] In some embodiments, graphene oxide and hollow carbon nanotubes are uniformly dispersed in an aqueous solution to form an aqueous solution containing graphene oxide and hollow carbon nanotubes, and then ethylenediamine is added and dispersed to form an aqueous solution containing graphene oxide, hollow carbon nanotubes and ethylenediamine.

[0053] Wherein, preferably, in the aqueous solution containing graphene oxide and hollow carbon nanotubes, the mass concentration of graphene oxide is 1mg / ml to 8mg / ml or 3mg / ml-4mg / ml, for example 2mg / ml, 3mg / ml, 4mg / ml, 5mg / ml, 6mg / ml, 7mg / ml or within the range formed by any two of the aforementioned values. Preferably, the dispersion method is magnetic stirring and / or ultrasonic dispersion. In some specific embodiments, the dispersion method is magnetic stirring and ultrasonic dispersion. There is no particular restriction on the conditions of magnetic stirring and ultrasonic dispersion, as long as the graphene oxide, hollow carbon nanotubes and ethylenediamine are uniformly dispersed in the aqueous solution.

[0054] In some embodiments, the mass ratio of graphene oxide to hollow carbon nanotubes is (5-20):1, such as 8:1, 10:1, 15:1, 18:1 or within the range formed by any two of the foregoing ratios.

[0055] In some embodiments, relative to 1 mL of ethylenediamine, the mass of the added graphene oxide is 0.03 g-0.3 g, for example, 0.06 g, 0.12 g, 0.25 g or within the range formed by any two of the foregoing values.

[0056] In step (2), the temperature of the hydrothermal treatment is 80-180°C or 100-140°C, such as 90°C, 120°C, 140°C, 160°C or within the range formed by any two of the aforementioned values. The time of the hydrothermal treatment can be 4-12h or 4-8h, such as 5h, 6h, 8h, 10h or within the range formed by any two of the aforementioned values. The equipment used for the hydrothermal treatment can be a hydrothermal kettle.

[0057] In step (3), the freezing temperature of freeze drying is -50°C to -60°C. The freezing time can be 45-52 hours. The drying method can be vacuum drying. The vacuum drying time can be 40-56 hours. After freeze drying the graphene oxide / carbon nanotube hydrogel, the graphene oxide / carbon nanotube aerogel is obtained.

[0058] The graphene oxide / carbon nanotube aerogel is further reduced to obtain a graphene / carbon nanotube aerogel. The reduction treatment can be performed by heating the graphene oxide / carbon nanotube aerogel in a microwave oven or reducing the hydrogel by ignition. For example, the hydrogel can be heated at a power of 500 to 900 W for 10 to 60 seconds. After freeze-drying and microwave treatment of the graphene oxide / carbon nanotube hydrogel, a graphene / carbon nanotube aerogel skeleton with high ionic conductivity and electronic conductivity can be obtained. The graphene / carbon nanotube aerogel of the present invention acts as a skeleton to play the role of a continuous conductive network and improve the rate performance. The hollow structure of the carbon nanotube can be used as a high-speed transmission channel for lithium / sodium ions to improve ionic conductivity.

[0059] In step (4), the mixture of graphene / carbon nanotube aerogel and resin is impregnated. The impregnation method can be positive pressure impregnation at 0.7-1.2MPa, such as 0.8-1.0MPa. The impregnation time can be 1 to 6h, such as 2-4h. The impregnation can be carried out in an impregnation furnace. Through positive pressure impregnation, the resin is completely filled into the graphene / carbon nanotube aerogel skeleton, ensuring the compaction density of the material. The resin can be selected from one or more of epoxy resin, phenolic resin, acrylic resin, polyurethane resin, polyester resin, alkyd resin, natural resin, UV resin, silicone resin, polyketone resin, aldehyde-ketone resin, amino resin, and fluorocarbon resin. In some embodiments, the resin is epoxy resin. Through impregnation, especially positive pressure impregnation, the resin can be more fully filled into the pore structure of the aerogel to ensure the compaction density of the material.

[0060] After the impregnation is completed, heat treatment is performed. The heat treatment is generally a low-temperature heat treatment, such as a heat treatment temperature of 90-200°C, such as 130-180°C. The treatment time of the heat treatment can be 1-6h, such as 0.5-3h. After the heat treatment is completed, a cured resin @ graphene oxide / carbon nanotube aerogel composite material is obtained. The particle size of the resin @ graphene oxide / carbon nanotube aerogel composite material can be coarsely crushed to less than 1mm (such as 0.1mm-1mm), and then pre-carbonized. The pre-carbonization method is generally heating treatment. The heating temperature of pre-carbonization is generally 300-600°C, such as 300-500°C. The treatment time of pre-carbonization can be 2-6h, such as 2-4h. Carbonization can be carried out under an inert atmosphere. After pre-carbonization, a resin-based hard carbon precursor is obtained.

[0061] In step (5), the resin-based hard carbon precursor can be first crushed to a target particle size Dv50 of 3-8 μm, and then carbonized to obtain a resin-based hard carbon material. The carbonization treatment is generally performed by heating. The heating temperature of the carbonization treatment can be 900-1500° C., such as 1000-1400° C. The carbonization treatment time can be 2-6 hours, such as 3-5 hours.

[0062] Therefore, the present invention provides a resin-based hard carbon material, which is prepared by the method described above. In the resin-based hard carbon material of the present invention, the graphene / carbon nanotube aerogel in the graphene oxide / carbon nanotube hydrogel serves as a skeleton, playing the role of a continuous conductive network; the hollow structure of the carbon nanotube can serve as a high-speed transmission channel for lithium / sodium ions, thereby improving ion conductivity; thereby improving the rate performance of the resin-based hard carbon material of the present invention.

[0063] Negative plate

[0064] The present invention also provides a negative electrode sheet, which includes a negative electrode current collector and a negative electrode active material layer. The negative electrode slurry including the resin-based hard carbon material, the conductive agent and the binder as described herein is applied to the surface of the negative electrode current collector, and then dried and pressed to form the negative electrode active material layer. In some embodiments, the surface density of the negative electrode active material layer is 2-10 mg / cm 2 or 5-7 mg / cm 2 . The compacted density is 0.8-1.1g / cm 3 .

[0065] The material of the negative electrode current collector is not particularly limited, and conventional negative electrode current collectors in the art, such as copper foil or aluminum foil, may be used.

[0066] The negative electrode conductive agent may be one or more selected from acetylene black, carbon nanotubes, carbon black, and conductive graphite. The negative electrode binder may be one or more selected from polytetrafluoroethylene emulsion (PTFE), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), polyacrylic acid (PAA), and polyvinylidene fluoride emulsion (PVDF).

[0067] The mass ratio of each component in the negative electrode active material layer can be conventional, for example, the mass fraction of the resin-based hard carbon material described herein can be 90%-98%, such as 91%, 92%, 93%, 95%, 95.7%, 96%, 97%. The mass fraction of the conductive agent can be 0.5%-5%, such as 1%, 1.5%, 2%, 3%, 4%. The mass fraction of the binder can be 0.5%-5%, such as 1%, 1.5%, 2%, 3%, 4%.

[0068] Electrochemical Devices

[0069] The electrochemical device of the present application is, for example, a primary battery, a secondary battery, a fuel cell, a solar cell or a capacitor. The primary battery is, for example, a sodium ion primary battery. The secondary battery is, for example, a sodium ion secondary battery.

[0070] Sodium-ion batteries

[0071] In some embodiments, the sodium ion battery comprises a positive electrode sheet, a negative electrode sheet as described herein, a separator, and an electrolyte. The negative electrode sheet as described herein is applicable to various types of sodium ion batteries.

[0072] The positive electrode sheet includes a positive electrode current collector and a positive electrode material layer formed on the surface of the positive electrode current collector. The positive electrode material layer includes a positive electrode active material, a conductive agent and a binder. The positive electrode material layer is obtained by coating a positive electrode slurry containing a positive electrode active material, a conductive agent, a binder and a solvent on the positive electrode current collector, and rolling and baking. The positive electrode current collector can be copper foil, aluminum foil, titanium foil, nickel foil, iron foil, zinc foil, etc. The solvent of the positive electrode slurry can be N-methylpyrrolidone (NMP). The positive electrode active material can be conventionally used in sodium ion batteries in the art, for example, at least one of a transition metal layered oxide, a polyanion compound and a Prussian blue compound that can reversibly remove and embed sodium. The conductive agent of the positive electrode can be at least one selected from conductive carbon black (SP), carbon fiber (CF), acetylene black, Ketjen black, graphene and carbon nanotubes. The binder of the positive electrode can be at least one selected from fluorine-containing resin, polypropylene resin, fiber-type binder, rubber-type binder and polyimide-type binder. In some embodiments, the conductive agent in the positive electrode material layer is SP and the binder is PVDF. The content ratio of each component in the positive electrode material layer can be conventional, for example, the mass fraction of the positive electrode active material can be 90%-98%, such as 92%, 94%, 95%, 96%, 96.7%, 97%, 97.5%. The mass fraction of the conductive agent can be 1%-5%, such as 1.2%, 1.3%, 1.5%, 2%, 3%, 3.5%, 4%. The mass fraction of the binder can be 1%-5%, such as 1.2%, 1.5%, 1.8%, 2%, 2.5%, 3%, 4%.

[0073] The separator can be selected from various separators used in sodium ion batteries known to those skilled in the art, including but not limited to polyethylene, glass fiber, polypropylene separator, etc.

[0074] The electrolyte is composed of a non-aqueous organic solvent and a sodium salt. The non-aqueous organic solvent can be at least one selected from a carbonate-based solvent, an ether-based solvent, and a ketone-based solvent. In particular, the non-aqueous organic solvent can be an aprotic organic solvent such as propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, cyclopentane, methyl cyclopentane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate. The sodium salt can be a material that is easily soluble in the non-aqueous solvent. Examples include, but are not limited to, NaCl, NaBr, NaI, NaClO4, NaBF4, NaPF6, NaCF3SO3, NaCF3CO2, NaAsF6, NaSbF6, NaAlCl4, CH3SO3Na, (CF3SO2)2NNa.

[0075] The button-type sodium ion battery can be obtained by assembling the positive electrode sheet and the negative electrode sheet in the order of the negative electrode shell, the spring sheet, the gasket, the sodium sheet, the electrolyte, the diaphragm, the electrolyte, the negative electrode sheet and the positive electrode shell.

[0076] Lithium-ion battery

[0077] In some embodiments, the lithium ion battery comprises a positive electrode, a negative electrode as described herein, a separator, and an electrolyte. In the present invention, the structure of the lithium ion battery, the positive electrode, the separator, the electrolyte, and the method for making the lithium ion battery can be conventional in the art.

[0078] The present invention will be described below in the form of specific examples. It should be understood that these examples are merely illustrative and are not intended to limit the scope of the present invention. The methods, reagents and materials used in the examples are, unless otherwise stated, conventional methods, reagents and materials in the art. The raw material compounds in the examples can all be purchased through commercial routes.

[0079] Example 1

[0080] Preparation of high-magnification composite resin-based hard carbon materials

[0081] (1) 1.5 g of graphene oxide and 0.15 g of hollow carbon nanotubes were added to 500 ml of deionized water, magnetically stirred for 12 h, and ultrasonically dispersed for 2 h to form a uniformly dispersed aqueous solution of graphene oxide / carbon nanotubes, wherein the concentration of graphene oxide was 3 mg / ml; 40 ml of the graphene oxide / carbon nanotube solution was placed in a 50 ml hydrothermal reactor, 1 ml of ethylenediamine solution was added, and stirred evenly to obtain an aqueous solution of graphene oxide, hollow carbon nanotubes and ethylenediamine. The mass ratio of graphene oxide to hollow carbon nanotubes was 10:1.

[0082] (2) The aqueous solution is heated at 120° C. for 6 h to obtain graphene oxide / carbon nanotube hydrogel.

[0083] (3) The graphene oxide / carbon nanotube hydrogel was then freeze-dried at -55 °C for 48 h and then heated in a 700 W microwave oven for 45 s to obtain graphene / carbon nanotube aerogel.

[0084] (4) Graphene / carbon nanotube aerogel and epoxy resin were mixed, and the resulting mixture was impregnated in an impregnation furnace at a pressure of 0.9 MPa for 3 h. After impregnation, the mixture was heat treated (cured) at 160°C for 1 h to obtain a cured resin@graphene oxide / carbon nanotube aerogel composite material. The resin@graphene oxide / carbon nanotube aerogel composite material was coarsely crushed to less than 1 mm and heat treated (pre-carbonized) at 400°C for 3 h to obtain a composite resin-based hard carbon precursor.

[0085] (5) The composite resin-based hard carbon precursor was crushed by air flow mill to a Dv50 of 5 μm, and then heat treated (carbonized) at 1300°C for 4 h to obtain a high-ratio composite resin-based hard carbon material.

[0086] Negative electrode preparation

[0087] The high-rate composite resin-based hard carbon material, conductive carbon black, hydroxymethyl cellulose and styrene-butadiene rubber prepared above are dispersed in deionized water to form a negative electrode active material slurry. Among them, the weight ratio of high-rate composite resin-based hard carbon material: conductive carbon black: hydroxymethyl cellulose: styrene-butadiene rubber is 92%: 3%: 2%: 3%. The slurry is coated on copper foil and then dried at 100°C for 10 minutes to form a negative electrode active material layer, thereby preparing a negative electrode sheet. The surface density of the negative electrode active material layer after drying is 8 mg / cm 2 , compacted density is 0.9g / cm 3 .

[0088] Example 2

[0089] The difference from Example 1 is that in step (1), the concentration of graphene oxide in the aqueous solution of graphene oxide / carbon nanotubes is 2 mg / ml. The mass ratio of graphene oxide to hollow carbon nanotubes is 10:1. The remaining operating conditions and steps are the same as those in Example 1.

[0090] Example 3

[0091] The difference from Example 1 is that in step (1), the concentration of graphene oxide in the aqueous solution of graphene oxide / carbon nanotubes is 4 mg / ml. The mass ratio of graphene oxide to hollow carbon nanotubes is 10:1. The remaining operating conditions and steps are the same as those in Example 1.

[0092] Example 4

[0093] The difference from Example 1 is that in step (1), the concentration of graphene oxide in the aqueous solution of graphene oxide / carbon nanotubes is 3 mg / ml. The ratio of graphene oxide to hollow carbon nanotubes is 20:1. The remaining operating conditions and steps are the same as those in Example 1.

[0094] Example 5

[0095] The difference from Example 1 is that in step (1), the concentration of graphene oxide in the aqueous solution of graphene oxide / carbon nanotubes is 3 mg / ml. The ratio of graphene oxide to hollow carbon nanotubes is 5:1. The remaining operating conditions and steps are the same as those in Example 1.

[0096] Example 6

[0097] The difference from Example 1 is that in step (4), the heating temperature for pre-carbonization is 300°C.

[0098] Example 7

[0099] The difference from Example 1 is that in step (4), the heating temperature for pre-carbonization is 600°C.

[0100] Example 8

[0101] The difference from Example 1 is that in step (5), the heating temperature of the carbonization treatment is 900° C.; and the time of the carbonization treatment is 6 hours.

[0102] Example 9

[0103] The difference from Example 1 is that in step (5), the heating temperature of the carbonization treatment is 1500° C.; and the time of the carbonization treatment is 2 h.

[0104] Example 10

[0105] The difference from Example 1 is that in step (4), the immersion pressure is 0.7 MPa and the immersion time is 6 h.

[0106] Embodiment 11

[0107] The difference from Example 1 is that in step (4), the immersion pressure is 1.2 MPa and the immersion time is 1 h.

[0108] Example 12

[0109] The difference from Example 1 is that in step (4), the temperature of the heat treatment is 90° C. and the treatment time of the heat treatment is 6 hours.

[0110] Embodiment 13

[0111] The difference from Example 1 is that in step (4), the temperature of the heat treatment is 200° C.; and the treatment time of the heat treatment is 0.5 h.

[0112] Embodiment 14

[0113] The difference from Example 1 is that in step (5), the Dv50 of the precursor after airflow pulverization is 3 μm.

[0114] Embodiment 15

[0115] The difference from Example 1 is that in step (5), the Dv50 of the precursor after airflow pulverization is 8 μm.

[0116] Comparative Example 1

[0117] The difference from Example 1 is that graphene / carbon nanotube aerogel is not prepared, and only epoxy resin is cured and heat treated to prepare hard carbon. The curing temperature is 160°C and the curing time is 1h. The cured resin is coarsely crushed to less than 1mm and heat treated at 400°C for 3h to obtain a resin hard carbon precursor. The resin-based hard carbon precursor is crushed with a jet mill to a Dv50 of 5μm, and then heat treated at 1300°C for 4h to obtain a resin-based hard carbon material.

[0118] Comparative Example 2

[0119] The difference from Example 1 is that in step (1), no hollow carbon nanotubes are added.

[0120] Test Case

[0121] The negative electrode sheets obtained in the above examples and comparative examples were used as negative electrode sheets of sodium ion batteries to make button-type sodium ion secondary batteries, and the battery performance tests were carried out:

[0122] (1) Preparation of positive electrode

[0123] The positive electrode active material Na1.0 Ni 0.33 Fe 0.33 Mn 0.34 O2, conductive carbon black (SP), and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of positive electrode active material: conductive agent: PVDF = 95:2:3 with N-methylpyrrolidone as solvent to make positive electrode slurry, and the positive electrode slurry is evenly coated on a 16-micron thick aluminum foil, dried, rolled, and cut to make positive electrode sheets.

[0124] (2) Diaphragm: PP diaphragm.

[0125] (3) Preparation of electrolyte: The solvent is a mixed solution of ethylene carbonate and propylene carbonate (mass ratio is 1:1), and the solute is 1 mol / L sodium salt NaClO4.

[0126] (4) Preparation of sodium ion secondary batteries

[0127] The button-type sodium ion secondary battery is manufactured by assembling the negative electrode shell, the spring sheet, the gasket, the positive electrode sheet, the electrolyte, the diaphragm, the electrolyte, the negative electrode sheet and the positive electrode shell in this order.

[0128] (5) Ratio test

[0129] ① Leave for 12 hours;

[0130] ②0.1C constant current discharge to 0V;

[0131] ③Stay still for 5 minutes;

[0132] ④0.1C constant current charging to 2V;

[0133] ⑤Stay still for 5 minutes;

[0134] ⑥5C constant current discharge to 0V;

[0135] ⑦Stay still for 5 minutes;

[0136] ⑧5C constant current charging to 2V.

[0137] (6) Cycle test

[0138] ① Leave for 12 hours;

[0139] ②0.1C constant current discharge to 0V;

[0140] ③Stay still for 5 minutes;

[0141] ④0.1C constant current charging to 2V;

[0142] ⑤Stay still for 5 minutes;

[0143] ⑥1C constant current discharge to 0V;

[0144] ⑦Stay still for 5 minutes;

[0145] ⑧1C constant current charging to 2V;

[0146] ⑨Stay still for 5 minutes;

[0147] ⑩ Steps 2-5 are repeated 500 times, and the 500th discharge capacity is recorded as C500.

[0148] The preparation process conditions of the embodiment and the comparative example are shown in Table 1. The performance results of the measured batteries are shown in Table 2.

[0149] Table 1. Preparation process conditions

[0150]

[0151]

[0152] Table 2. Comparison of electrical performance results

[0153]

[0154]

[0155] It can be seen from the test results of Comparative Examples 1, 2 and Example 1 in Table 2 that when the resin is compounded with the graphene / carbon nanotube conductive substrate, the rate and cycle performance of the resin-based hard carbon are significantly improved. It can be seen from Examples 1, 2, and 3 that with the increase of the graphene and carbon nanotube conductive networks, the rate performance and cycle gradually improve, but the increase in performance of the excessive conductive network is not obvious. It can be seen from Examples 1, 4, 5 and Comparative Example 2 that the addition of carbon nanotubes significantly improves the rate performance, but agglomeration will occur after a single excessive increase, and the rate performance improvement is not obvious. It can be seen from Examples 1, 6, and 7 that the pre-carbonization temperature will affect the microstructure of the material, and lowering or increasing the pre-carbonization temperature will deteriorate the rate and cycle performance. It can be seen from Examples 1, 8 and 9 that a lower carbonization temperature is not conducive to the formation of disordered graphite crystallites, which will significantly deteriorate the capacity and cycle performance, and a higher carbonization temperature will reduce the interlayer spacing of the carbon layer, which will affect the rate performance. It can be seen from Examples 1, 10, and 11 that the same performance can be achieved by lowering the impregnation pressure to extend the impregnation time and by increasing the impregnation pressure to shorten the impregnation time; it can be seen from Examples 1, 12, and 13 that too low a curing temperature is not conducive to the formation of the resin structure and will have a greater impact on the performance, and the same performance can be achieved by increasing the curing temperature and shortening the curing time; it can be seen from Examples 1, 14, and 15 that reducing the particle size to 3 μm can greatly shorten the ion transmission distance, thereby improving the rate performance and cycle performance, and increasing the particle size to 8 μm increases the ion transmission distance, and the rate performance and cycle performance decrease significantly.

[0156] Although the present invention has been disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.

Claims

1. A method for preparing a resin-based hard carbon material, characterized in that: It includes the following steps: S1, mixing graphene / carbon nanotube aerogel and resin, impregnating, heat treating and pre-carbonizing to obtain a resin-based hard carbon precursor; S2. Crushing and carbonizing the resin-based hard carbon precursor to obtain the resin-based hard carbon material.

2. The method according to claim 1, characterized in that The preparation of the graphene / carbon nanotube aerogel comprises the following steps: The graphene oxide / carbon nanotube hydrogel is freeze-dried and reduced to obtain a graphene / carbon nanotube aerogel; The method for obtaining the graphene / carbon nanotube hydrogel comprises the following steps: subjecting an aqueous solution containing graphene oxide, hollow carbon nanotubes and ethylenediamine to hydrothermal treatment to obtain the graphene oxide / carbon nanotube hydrogel.

3. The method according to claim 2, characterized in that The method has one or more of the following features: Adding ethylenediamine to a mixed aqueous solution containing graphene oxide and hollow carbon nanotubes to form an aqueous solution containing graphene oxide, hollow carbon nanotubes and ethylenediamine; wherein the mass concentration of graphene oxide in the mixed aqueous solution containing graphene oxide and hollow carbon nanotubes is 1 mg / ml to 8 mg / ml; The mass ratio of the graphene oxide to the hollow carbon nanotube is (5-20):1; and Relative to 1 mL of ethylenediamine, the mass of the added graphene oxide is 0.03 g-0.3 g.

4. The method according to claim 2, characterized in that The method has one or more of the following features: The temperature of the hydrothermal treatment is 80-180°C; The hydrothermal treatment time is 4-12h; The freeze drying temperature is -50°C to -60°C; The reduction treatment is carried out by heating.

5. The method according to claim 1, characterized in that The method has one or more of the following features: In step S1, the resin is selected from one or more of epoxy resin, phenolic resin, acrylic resin, polyurethane resin, polyester resin, alkyd resin, natural resin, UV resin, silicone resin, polyketone resin, aldehyde-ketone resin, amino resin and fluorocarbon resin; In step S1, the impregnation method is positive pressure impregnation, and the pressure of the positive pressure impregnation is preferably 0.7MPa to 1.2MPa; the impregnation time is 1 to 6h; In step S1, the temperature of the heat treatment is 90-200°C; the treatment time of the heat treatment is 0.5-6h; and In step S1, the pre-carbonization heating temperature is 300-600°C; the pre-carbonization time is 2-6h.

6. The method according to claim 1, characterized in that In step S2, the Dv50 of the crushed resin-based hard carbon precursor is 3-8 μm; and / or In step S2, the heating temperature of the carbonization treatment is 900-1500°C; the time of the carbonization treatment is 2-6 hours.

7. A resin-based hard carbon material prepared by the method according to any one of claims 1 to 6.

8. A negative electrode sheet comprising a negative electrode current collector and a negative electrode active material layer, characterized in that: The negative electrode active material layer comprises a negative electrode active material, a conductive agent and a binder, wherein the negative electrode active material comprises the resin-based hard carbon material as claimed in claim 7; preferably, the surface density of the negative electrode active material layer is 2-10 mg / cm 2 , compacted density is 0.8-1.1g / cm 3 .

9. An alkali metal ion battery, characterized in that: It comprises the negative electrode sheet as claimed in claim 7; preferably, the alkali metal ion battery is a sodium ion secondary battery.

10. Use of the resin hard carbon negative electrode material according to claim 7 in improving the rate and cycle performance of a battery, or in preparing a sodium ion battery or a lithium ion battery.

Citation Information

Patent Citations

  • High-performance resin-based hard carbon negative electrode material and preparation method and application thereof

    CN117682503A